Pengembangan Sistem Pengaduan Layanan Masyarakat Menggunakan Metode Rapid Application Development (RAD) - Yanuardi Yanuardi; Lukman Azhari; Alfry Aristo Jansen Sinlae; Allan Desi Alexander (LPPM STIKI MALANG, 2024)
The digital era has demanded efficient and responsive public services as a fundamental need for society, including in the aspect of service complaints. With the village office acting as an intermediary between the government and the public, challenges such as convoluted complaint procedures, lack of transparency, and resource limitations hinder the provision of responsive services. This research aims to address these issues through the development of a community service complaint system based on a website using the Rapid Application Development (RAD) method. RAD method was chosen for its ability to develop systems efficiently, with active user involvement, ensuring the system meets user needs. The research outcome is a community service complaint system based on a website, allowing the public to easily submit complaints, monitor their status, and view responses, while enabling officers to manage complaint data and provide direct responses. Usability testing of the system yielded an average score of 90.83%, indicating a high level of user satisfaction.